2013
DOI: 10.1111/gcb.12209
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and precipitation drive temporal variability in aquatic carbon and GHG concentrations and fluxes in a peatland catchment

Abstract: Biology, 19 (7). 2133-2148. 10.1111/gcb.12209 Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. Accepted ArticleThis article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
139
6
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(180 citation statements)
references
References 73 publications
(97 reference statements)
26
139
6
1
Order By: Relevance
“…Therefore, rainfall events strongly affect the phenology and growth of alpine plants and CO 2 effluxes. Our results agreed with those of Vargas et al (2012) and Dinsmore et al (2013); i.e., changes in the amount and frequency of rainfall are biophysical drivers that regulate the strength and timing of soil CO 2 efflux. Thus, the accurate quantification of terrestrial C sinks must consider interannual variations in temperature and precipitation.…”
Section: Responses Of Ecosystem and Soil Respiration To Nutrient Fertsupporting
confidence: 89%
“…Therefore, rainfall events strongly affect the phenology and growth of alpine plants and CO 2 effluxes. Our results agreed with those of Vargas et al (2012) and Dinsmore et al (2013); i.e., changes in the amount and frequency of rainfall are biophysical drivers that regulate the strength and timing of soil CO 2 efflux. Thus, the accurate quantification of terrestrial C sinks must consider interannual variations in temperature and precipitation.…”
Section: Responses Of Ecosystem and Soil Respiration To Nutrient Fertsupporting
confidence: 89%
“…The net ecosystem carbon balance (NECB) of individual northern latitude catchments has shown them to be net sinks for carbon (Dinsmore et al, , 2013bKoehler et al, 2011;Nilsson et al, 2008;Olefeldt et al, 2012;Roulet et al, 2007). In boreal forest catchments, carbon export via the aquatic pathway (consisting of dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), particulate organic carbon (POC) plus dissolved and gaseous CO 2 and CH 4 ) accounted for 4-28 % of carbon uptake via net ecosystem exchange (NEE), representing an im-…”
Section: Introductionmentioning
confidence: 99%
“…In boreal region, the model result showed that about half of annual carbon export occurred in the spring snowmelt period , and this implies the close relation to biological productivity in the soil-plant system, as suggested by Dinsmore et al (2013). The simulated results of discharge underestimated the previous data, whereas the simulated horizontal carbon transports generally overestimated the previous materials.…”
Section: Seasonal Variation Of Carbon Cycle In Regional Scalementioning
confidence: 63%